Two new species of the genus Ocellarnaca Gorochov, 2004 (Orthoptera: Gryllacrididae) from China - Duan, Yue-Ting; Chen, Po-Wei; Shi, Fu-Ming (Zootaxa, 2023)
The paper reports two new species of the genus Ocellarnaca Gorochov, 2004 (Orthoptera: Gryllacrididae) from China, i.e. Ocellarnaca longiprotubera sp. nov. and Ocellarnaca grossa sp. nov. The type specimens are deposited in the Museum of Hebei University, Baoding 071002, China.